Manusia dan lingkungan alam: Analisis faktor konfirmatori terhadap Nature Relatedness Scale Bahasa Indonesia - Bartolomeus Yofana Adiwena; Ratna Djuwita (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
The relationship or closeness between humans and the natural environment is a psychological construct that can be used to overcome environmental problems nowadays. Nature Relatedness Scale (NRS) is a questionnaire used to measure the relationship between humans and the natural environment, which is proven to be related to pro-environment behavior. However, there are no studies that have adapted and analyzed the structure of NRS in Indonesia, so that it can be used for studies on environmental psychology in Indonesia. This study aims to test the construct validity and reliability of NRS Bahasa Indonesia using confirmatory factor analysis (CFA) with a sample of Indonesian people (N= 174). The result shows that NRS Bahasa Indonesia has the same factor structure as the original NRS, namely: NR Self, NR Perspective, and NR Experience and can be used in research with a population of Indonesian people. NR Self and NR Experience have good construct reliability and validity, while NR Perspective has moderate construct reliability and validity. The potential of the NRS to investigate pro-environmental concerns and behavior, as well as suggestions for further research are discussed.